2016
DOI: 10.2119/molmed.2016.00130
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hsp70 and Glutamine in Pediatric Severe Malaria Anemia: Role of hemozoin in Suppressing Hsp70 and NF-κB Activation

Abstract: Severe malarial anemia (SMA; hemoglobin [Hb] <5.0 g/dL) is a leading global cause of morbidity and mortality among children residing in Plasmodium falciparum transmission regions. Exploration of molecular pathways through global gene expression profiling revealed that SMA was characterized by decreased HSPA1A, a heat shock protein 70 (Hsp70) coding gene. Hsp70 is a ubiquitous chaperone that regulates nuclear factor-kappa B (NF-κB) signaling and production of proinflammatory cytokines known to be important in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 85 publications
1
19
0
Order By: Relevance
“…Binding of C1q to LAIR1 inhibits cellular activation and prevents the production of cytokines containing NF-κB and IRAF promoter response elements [41]. Our previous studies demonstrate that treatment of PBMCs with Pf Hz induces NF-κB activation and cytokine production [42]. Since phagocytosis of Pf Hz decreased LAIR1 transcription in cultured PBMCs, and blocked the induction of pLAIR1 by C1q, we determined the effect of C1q on pNF-κB p65 in Pf Hz-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Binding of C1q to LAIR1 inhibits cellular activation and prevents the production of cytokines containing NF-κB and IRAF promoter response elements [41]. Our previous studies demonstrate that treatment of PBMCs with Pf Hz induces NF-κB activation and cytokine production [42]. Since phagocytosis of Pf Hz decreased LAIR1 transcription in cultured PBMCs, and blocked the induction of pLAIR1 by C1q, we determined the effect of C1q on pNF-κB p65 in Pf Hz-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Still, preclinical testing will be required to explore the possible benefits of such interventions, as the complexity of host-parasite interactions makes the outcomes and possible unexpected adverse consequences difficult to predict (59). For example, iron supplementation administered in a clinical trial for malarial anemia resulted in increased mortality (59), and elevated plasma glutamine has been associated with both better outcomes in the context of malarial anemia (60) and poor outcomes in the context of cerebral malaria (61). LysoPC administration, which is currently under investigation as an adjunctive therapy for sepsis (62), may prove useful in malaria for both treating acute disease and reducing transmissibility (58).…”
Section: Discussionmentioning
confidence: 99%
“…https://doi.org/10.1371/journal.ppat.1008930.g001 glutamine levels are depleted in the human host in both falciparum and vivax malaria [9,21,22,28]. In addition to impacting arginine biosynthesis ( Fig 1A), low plasma glutamine has been associated with severe malarial anemia in children with P. falciparum [29] and with impaired humoral immunity in a murine model of severe malaria [27]. Conversely though, inhibiting glutamine metabolism is associated with increased survival in a murine model of late stage cerebral malaria (CM) via reducing immune-mediated pathology in the brain [30].…”
Section: Bloodstream Amino Acid and Glucose Perturbations In Malariamentioning
confidence: 99%
“…Studies comparing the metabolome of malaria with non-malarial febrile illnesses have identified both common and distinct features of malaria [ 9 , 52 ]. RDTs that include both Plasmodium infection markers (e.g., elevated pipecolic acid [ 45 ] and pinene [ 46 ]) and disease severity markers (e.g., depleted arginine [ 16 ], glutamine [ 29 ], and citrulline [ 17 ]) could have diagnostic and prognostic benefit.…”
Section: Introductionmentioning
confidence: 99%